Application of balloon guide catheter in emergency endovascular thrombectomy for large vessel occlusion - LUO Lei⁃lei; ZHAO Jian⁃bin; WEI Ming (Chinese Journal of Contemporary Neurology and Neurosurgery)
Endovascular thrombectomy is a first ⁃ line treatment option for acute large vessel occlusive ischemic stroke after strict selection, which is an effective method to improve the good prognosis rate of patients. More and more evidence⁃based medicine proves that balloon guide catheter (BGC) can shorten the reperfusion time, increase the rate of initial reperfusion, and reduce the risk of distal embolism due to it's proximal blood flow occlusion, but the application of BGC in emergency endovascular thrombectomy is still limited. This review summarizes the clinical application progress of BGC to provide theoretical basis for it's application in emergency endovascular thrombectomy.